2008
DOI: 10.1007/s12185-007-0019-6
|View full text |Cite
|
Sign up to set email alerts
|

The value of oral cytarabine ocfosfate and etoposide in the treatment of refractory and elderly AML patients

Abstract: Twenty-one acute myeloid leukemia (AML) patients were enrolled and received oral induction therapy with cytarabine ocfosfate (SPAC) and etoposide (EP). The median age was 69 years (range: 33-86). There were 11 patients with de novo AML and 10 AML cases that had evolved from myelodysplastic syndromes. Seventeen patients had abnormal karyotypes including eight complex abnormalities, various complications, and 7 of 21 had a poor performance status (PS) with Eastern Cooperative Oncology Group (ECOG) scores of 3-4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…1 and 10) with longer-lasting nadirs responded well to this treatment. Although ara-C levels were not measured in these MDS patients, a previous report states that the plasma concentration of ara-C is comparatively higher in AML patients with SPAC and EP combination therapy [8]. It is possible that the higher ara-C concentrations cause more marked myelosuppression and induce a reduction of leukemic blasts.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…1 and 10) with longer-lasting nadirs responded well to this treatment. Although ara-C levels were not measured in these MDS patients, a previous report states that the plasma concentration of ara-C is comparatively higher in AML patients with SPAC and EP combination therapy [8]. It is possible that the higher ara-C concentrations cause more marked myelosuppression and induce a reduction of leukemic blasts.…”
Section: Discussionmentioning
confidence: 92%
“…SPAC, at a dose of 300 mg/day, provides a pharmacokinetic profile similar to that of low-dose intravenous administration of ara-C (20 mg/m 2 /day) [8,21]. Several clinical trials using SPAC to treat AML and MDS [22,23,24] have shown the effectiveness of this regimen at doses of 100-400 mg/day for more than 14 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Off-target toxicities limited dose-escalation in these studies as well [45, 46]. A small combination study of orally administered cytarabine ocfosfate and etoposide showed higher induction of complete remission in treating patients with hematological malignancies compared to previous single agent or combination trials [47], and two recent follow-up studies supported these findings [48, 49]. …”
Section: Lipid-drug Conjugate Chemistrymentioning
confidence: 99%